Effect of volume fraction of LPSO phases on corrosion and mechanical properties of Mg-Zn-Y alloys. (5th May 2017) - Li, C.Q.; Xu, D.K.; Zeng, Z.R.; Wang, B.J.; Sheng, L.Y.; Chen, X.-B.; Han, E.H.
Abstract: Microstructural evolution, corrosion behavior and mechanical properties of cast Mg-Zn-Y alloys as a function of volume fraction of long period stacking ordered (LPSO) phases were investigated. Results revealed that 18R-LPSO phase was formed in Mg-0.9%Zn-1.6%Y (ZW12), Mg-2.1%Zn-5.2%Y (ZW25) and Mg-3.1%Zn-7.6%Y (ZW38) alloys. LPSO phases in these alloys acted as micro-cathode to accelerate corrosion progress due to their nobler nature than that of α-Mg matrix. The galvanic-couple effect between LPSO phases and α-Mg matrix dominated the corrosion rate of the cast Mg-Zn-Y alloys in the long-term corrosion process. As a result, ZW12 alloy displayed the best corrosion resistance due to the least volume fraction of micro-cathodes ( i.e. LPSO phases). In addition, compared with ZW25 alloy, the compact and thick LPSO phases in ZW38 alloy hindered the corrosion progress to a small degree since it was not preferentially oriented against corrosion front. The shape of corrosion pits was correlated to the shape of Mg dendrites that was a result of the volume fraction and distribution of LPSO phases. LPSO phases could enhance mechanical strength, but the increment was slight when the volume fraction of LPSO phases reached up to 20.3%. Graphical abstract: Highlights: Galvanic corrosion dominates corrosion resistance of Mg-Zn-Y alloys. Corrosion pits are related to the quantity and distribution of LPSO phases. Corrosion films on the LPSO phases and Mg matrix are different. Strength is improved slightly when the concentration of LPSO phases exceeds 20.3%.